Functional behaviour of TiO2 films doped with noble metals. (2nd August 2016) - Rodrigues, M. S.; Borges, J.; Gabor, C.; Munteanu, D.; Apreutesei, M.; Steyer, P.; Lopes, C.; Pedrosa, P.; Alves, E.; Barradas, N. P.; Cunha, L.; Martínez-Martínez, D.; et al.
Abstract : To evaluate the effects of different concentrations of noble metal in a TiO2 matrix, different films of both Ag/TiO2 and Au/TiO2 systems were prepared. Mechanical and tribological characterisation was carried out to evaluate the coating response as a function of the noble metal composition and (micro)structure of the films. The overall set of results indicates that the amorphous films reveal better results than the crystalline ones. For the amorphous samples, the reduced Young's modulus and the adhesion critical loads followed similar tendencies in both sets of films. Wear rates were similar for all samples except for the one with the highest silver content. To improve brittleness of TiO2 films, the results seem to indicate that a slight metal doping is preferred, and Au proved to be a better choice than Ag. In fact, the sample with the lowest Au content revealed a better mechanical behaviour than the pure TiO2 film.